2008
DOI: 10.1002/marc.200800501
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Self‐Doped Polyaniline Micro/Nanostructures: Microspheres, Aligned Pearls, and Nanotubes

Abstract: Hollow self‐doped polyaniline (SPAN) micro/nanostructures, such as hollow microspheres, aligned pearls, and nanotubes, have been synthesized by a one‐step chemical oxidation copolymerization of aniline (AN) and m‐aminobenzenesulfonic acid (SAN) using ammonium peroxydisulfate (APS) as the oxidant in aqueous solution. The process is facile and free of any template, surfactant, and external dopants. The shapes and sizes of the hollow SPAN micro/nanostructures can be controlled by adjusting the synthetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…It was previously suggested that copolymerization occurs due to a promoting effect of An cation radicals, which are first formed and then attack ABSA to yield dimers [28]. Moreover, depending on the An:ABSA molar ratio, selfassembly of oligomers at early stages of copolymerization is also possible since ABSA has the function of surfactant, dopant, and a monomer/crosslinker [33]. The following acid-base equilibrium exists across the interface for the An:ABSA mixtures used in this study,…”
Section: Resultsmentioning
confidence: 98%
“…It was previously suggested that copolymerization occurs due to a promoting effect of An cation radicals, which are first formed and then attack ABSA to yield dimers [28]. Moreover, depending on the An:ABSA molar ratio, selfassembly of oligomers at early stages of copolymerization is also possible since ABSA has the function of surfactant, dopant, and a monomer/crosslinker [33]. The following acid-base equilibrium exists across the interface for the An:ABSA mixtures used in this study,…”
Section: Resultsmentioning
confidence: 98%
“…This group of 1 H NMR signals was initially observed in our previous work for further investigation of the fine structures and the structure‐property relations of the PANI samples,18 which were synthesized in the alkali‐guided system and this innovative synthesis method has attracted much attention of researchers and academics due to that it not only opens up a new way for the fabrication of PANI micro‐ and nanostructures, but also brings interesting insight for the mechanism discussion 19–25. The 1 H NMR detection is a common but important method to obtain some fine information about polymer.…”
Section: Introductionmentioning
confidence: 95%
“…During in situ polymerization, polyester fabric is introduced into acid solution with oxidant and aniline and a film made of polyaniline is formed on the surface of fabric. The in situ polymerization has many advantages, such as good spinnability, cost savings, good conductivity, and simple process (Cheng, 2002;Li, Zhang, Peng, Chen, Zhang, 2008;Marie Claude Bernard, 1999).…”
Section: Introductionmentioning
confidence: 98%